ANALISIS KELAYAKAN USAHA ASPEK FINANSIAL PENANGKAPAN MINI PURSE SEINE DENGAN UKURAN JARING YANG BERBEDA DI PPI UJUNGBATU KABUPATEN JEPARA - S.Pi., Pujianto; Boesono, Herry; Wijayanto, Dian (Fakultas Perikanan dan Ilmu Kelautan, Universitas Diponegoro, 2013)
Mini purse seine is a productive fishing gear in catching pelagic fishes. Potencial resources utilization could be increased by adding the size length and width of the nets. Therefore it needed to be analyzed the feasibility rate of those mini purse seines. The purposes of this research were to analyze study feasibility aspect (PP, R/C ratio, NPV, and IRR) of mini purse seine with nets different size in PPI Ujungbatu Jepara Regency and to analyze nets different size impact against NPV, R/C ratio and IRR of mini purse seines in PPI Ujungbatu Jepara Regency. The method used in this research was descriptive method by case study and data was collected through direct observation, interviewed, and literature study. The results of feasibility aspect obtained that marine fisheries business using mini purse seine with length 450 m (width 90 m) the average values of PP, R/C ratio, NPV, and IRR were 2,22 years, 1,17, Rp.454.423.108,64, and 38,56%. Mean while in marine fishing business using mini purse seine with length of the nets 360 m (width 75 m) The analysis results of feasibility aspect obtained that the average values of PP, R/C ratio, NPV, and IRR were 2,25 years, 1,16, Rp.394.713.135,15, and 38,33%. From those analysis concluded that fishing business using mini purse seine with different size of nets in PPI Ujungbatu Jepara Regency are feasible.